Track II diplomacy (Its concept, mechanisms, strengths and weaknesses) - أبو العبد, أحمد; عصام اسماعيل,; رامي كاسر لايقة , (Latakia University Journal - Economic and Legal Sciences Series, 2023)
When global issues are too contentious or politically charged for governments, and with the complexity of internal conflicts and the extension of their actors and issues beyond the scope of the conflict zone, it has become difficult for official diplomacy carried out by states and regional and international governmental organizations to be alone in efforts to settle these conflicts, as what has emerged in parallel with it is the so-called Track Two Diplomacy, It is a term coined by the American diplomat Joseph Montville in 1981, referring to a broad range of unofficial contact and interaction aimed at resolving conflicts, both internationally and within states This research aims to study Track Two Diplomacyin terms of its concept, features, and its most prominent strengths and weaknesses. The research reached a set of results, most notably: Track Two Diplomacy is not a substitute for Track One Diplomacy, but it is a complementary system that takes advantage of resources and opportunities that are not available at the official level. Track Two, like any track in the multi-track system, will always be more effective when employed in conjunction and coordination with efforts from all of the other tracks, including Track One. Resolving deep-rooted social conflicts requires change -- change in attitudes, change in structures, and change in political and legal relationships. Change at the political level is for the most part the domain of Track One. True conflict resolution, however, is not sustainable through a single-track effort. Track Two diplomacy is a growing field, and with each new Track Two initiative there is an opportunity for cooperation and collaboration with Track One efforts. In the end, it is only through a collaborative effort among all societal sectors and power structures that real change is possible. Keywords: first track diplomacy, second track diplomacy, multi-track diplomacy,